SPM KESEHATAN MASAYARAKAT DALAM PENANGGULANGAN BENCANA ALAM SEBAGAI UPAYA PEMENUHAN HAM SESUAI DENGAN UU N0 36 TAHUN 2009 TENTANG KESEHATAN - Lalu Mariawan Alfarizi (UNISSULA, 2015)
The disaster problem , requiring an arrangement or planning in handling. So that it can be implemented in a focused and integrated. To provide a clear legal basis for national disaster then, the government has adopted the Law . 24 Year 2007 on disaster management which contains the basic provisions to include pre-disaster disaster management, emergency response and post-disaster. Natural disasters are traditionally seen as situations that pose various challenges and problems , especiallythe nature of humanity. Little attention is given tothe protection of human rights (Human Rights), which should also be present in this particular situation . It is necessary for thestudy of the minimum standard of health care as a natural disaster efforts to comply in accordance with the Human Rights Act 36 of 2009 on Health.The purpose of this study to determine the minimum standard of health care victims of natural disasters in Law No.36 of 2009 on health in accordance with human rights and the implementation of minimum standards of public health services of victims ofnatural disasters in central Lombok associated with Act 36 of 2009 on Health.This riset uses the following research : Methods normative juridical approach, deskriftip analytical nature of the data , secondary data , engineering data collection library. Results it can be concluded that :Minimum standard of health care victims of natural disasters in Act 36 of 2009 onHealth in accordance with the Human Rights and Implementation of a minimum standardof health care communities affected by natural disasters.